THE ROLE AND PLACE OF WOMEN IN THE SOCIETY ON THE TERRITORY OF EASTERN HALYCHYNA BEING THE PART OF ІІ POLISH-LITHUANIAN COMMONWEALTH (1920-1939) - Сасанчин, Володимир Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to consider the reasons for the widespread involvement of women in various fields of activity, in particular, in the police, and to find out their place and role in the police on the territory of Eastern Halychyna being the part of ІІ Polish-Lithuanian Commonwealth (1920-1939). Methods of the research: analysis, comparison and synthesis methods are applied in the research. Outcomes: it has been proved that the regular units of women police officers operating in the Police in Eastern Halychyna within the Republic of Poland during the 30s of the 20th century played a positive role in preventing and combating certain types of crimes during a short period of their existence and promoted the establishment of the police contacts with broad strata of society. Discussion: having drawn historical parallels, we can say that current women’s work in the police of any state, including Ukraine, is extremely important and necessary, however, both the methods of work and the activity management require improvement prompted by modern realities of life.